2023
DOI: 10.1097/dss.0000000000004002
|View full text |Cite
|
Sign up to set email alerts
|

The Controversy and Value of Mohs Micrographic Surgery for Melanoma and Melanoma in Situ on the Trunk and Extremities

John A. Zitelli,
Evan Stiegel,
David G. Brodland

Abstract: BACKGROUND The use of Mohs surgery for melanoma on the trunk and extremities is not supported in the guidelines of dermatology, but is widely used in the real world. OBJECTIVE The purpose of this article is to expose the value of Mohs surgery for melanoma on the trunk and extremities for consideration of updating the guidelines. MATERIALS AND METHODS This was a retrospective review of a prospectively maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The suggestion for margins greater than 5 mm follows concerning recurrence rates when only 5 mm margins are employed [ 28 , 29 ]. Guidelines now generally recommend a margin of 5 to 10 mm with the aim of achieving a complete histological clearance [ 23 , 30 ], while Mohs surgery may be used to obtain clear margins and reduce recurrence for MIS [ 31 , 32 , 33 ]. A recent systematic review concluded that outcomes with Mohs are comparable to WLE, but considered further evidence was required to confirm a precise role [ 34 ].…”
Section: Excision Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggestion for margins greater than 5 mm follows concerning recurrence rates when only 5 mm margins are employed [ 28 , 29 ]. Guidelines now generally recommend a margin of 5 to 10 mm with the aim of achieving a complete histological clearance [ 23 , 30 ], while Mohs surgery may be used to obtain clear margins and reduce recurrence for MIS [ 31 , 32 , 33 ]. A recent systematic review concluded that outcomes with Mohs are comparable to WLE, but considered further evidence was required to confirm a precise role [ 34 ].…”
Section: Excision Marginsmentioning
confidence: 99%
“…A recent systematic review concluded that outcomes with Mohs are comparable to WLE, but considered further evidence was required to confirm a precise role [ 34 ]. Mohs has even been studied as an option for invasive melanomas outside of face lesions [ 31 ].…”
Section: Excision Marginsmentioning
confidence: 99%
“…More importantly, preventing local recurrence is associated with reduced mortality created by unrecognized melanoma progression. [4][5][6] For instance, in a study of MIS recurrence on higher-risk sites, approximately 25% were found to be invasive melanoma on recurrence, with a median thickness of 0.37 to 0.94 mm. However, prevention of local recurrence must be balanced with considerations, such as access, cost, and the morbidity associated with larger excision margins.…”
mentioning
confidence: 99%
“…Preventing local recurrence is the primary goal of surgical excision and is associated with reduced cost, anxiety, and the need for repeated surgery. More importantly, preventing local recurrence is associated with reduced mortality created by unrecognized melanoma progression . For instance, in a study of MIS recurrence on higher-risk sites, approximately 25% were found to be invasive melanoma on recurrence, with a median thickness of 0.37 to 0.94 mm.…”
mentioning
confidence: 99%